A duplex droplet digital PCR assay for Salmonella and Shigella and its application in diarrheal and non-diarrheal samples. (July 2022) - Zhang, Jingyun; Huang, Yuanming; Xue, Panpan; Zhan, Zhifei; Huang, Zheng; Li, Jie; Diao, Baowei; Kan, Biao
Highlights: The duplex ddPCR assay targets Salmonella fimY and Shigella ipaH genes. LOD and LOQ of ddPCR were 550 and 5, 500 CFU/mL of stool sample for Shigella . Both LOD and LOQ were 1.0 × 10 4 CFU/mL of stool sample for Salmonella . ddPCR gave more positive results than qPCR in detecting stool samples. Salmonella load was higher in diarrheal samples than in non-diarrheal samples. Abstract: Objectives: To evaluate a duplex droplet digital polymerase chain reaction (ddPCR) assay targeting Salmonella fimY and Shigella ipaH genes. Methods: The linear range, precision, analytical sensitivity, and analytical specificity of the ddPCR assay were analyzed. The ddPCR assay was compared with quantitative real-time PCR (qPCR) using 362 stool samples from 187 children with mild diarrhea and 175 children without diarrhea. Results: The duplex ddPCR assay showed good linearity in the range of 5.3 × 10 0 to 1.24 × 10 5 copies/reaction for Salmonella and 1.9 × 10 0 to 1.84 × 10 5 copies/reaction for Shigella . When analyzed with spiked stool samples, the limit of detection and limit of quantification were 550 and 5500 colony-forming units per mL of stool sample for Shigella, respectively, whereas both were 1.0 × 10 4 colony-forming units per mL of stool sample for Salmonella . Among 362 stool samples, more samples were detected as positive by ddPCR than by qPCR. Salmonella load was significantly higher in diarrheal samples than in non-diarrheal samples. Determined by receiver-operating characteristic analysis, the optimal cut-off value was 1.25 × 10 4 copies/mL of stool sample to distinguish between symptomatic and asymptomatic Salmonella infections. Conclusion: Salmonella and Shigella prevalence may have been underestimated in the past.